PERAN KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK DALAM MENINGKATKAN MOTIVASI BELAJAR DI DESA TANAH TERBAN - Lisa Damayanti (Jurnal Anifa: Studi Gender dan Anak, 2021)
The purpose of this study was determine how the role of parent and child interpersonal communication in increasing learning motivation in Tanah Terban Village. The subjects in this study were 4 parents who have children aged 7-12 years. Based on the results of observations made in Tanah Terban Village, the researchers found that parents still do not understand how to provide good learning motivation to their children. Parents are also indifferent to children’s learning time which results in children watching television while doing homework, playing gadgets, and playing with their friends until they forget about studying and doing homework.